Expert opinion on the management of patients with osteoporosis with anabolic drugs in Italy - M. Rossini; F.P. Cantatore; A. Del Puente; B. Frediani; D. Gatti; S. Giannini; M. Varenna; O. Viapiana; G.D. Sebastiani (PAGEPress Publications, 2024)
Objective. Fragility fractures (FF) resulting from osteoporosis pose a significant public health challenge in Italy, with considerable socio-health and economic implications. Despite the availability of safe and effective drugs, osteoporosis remains underdiagnosed and undertreated, leaving over 2 million high-risk Italian women without treatment. This paper aims to identify and propose key improvements in the management of osteoporosis, focusing particularly on the critical issues related to the use of anabolic drugs in secondary prevention, according to the current Italian Medicines Agency (AIFA) Note 79. Methods. The Expert Panel, composed of nine recognized Italian experts in rheumatology, analyzed current practices, prescribing criteria, and the most recent literature. Three main reasons for revising the indications on pharmacological treatment of osteoporosis were identified: inadequate treatment of osteoporosis, new evidence regarding frontline placement of anabolics in high-risk conditions, and emerging sequential or combined strategies. Results. The proposed improvements include the adoption of the Derived Fracture Risk Assessment algorithm for accurate fracture risk assessment, revision of AIFA Note 79 to reflect current evidence, improved prescribing appropriateness, broader access to anabolic agents, and the provision of sequential therapies with antiresorptives for teriparatide. These changes aim to enhance patient outcomes, streamline healthcare processes, and address the high percentage of undertreated individuals. Conclusions. This expert opinion emphasizes the importance of the appropriate use of anabolic drugs to reduce FF and associated costs while ensuring the sustainability of the National Health Service. The proposed recommendations are in line with the latest scientific evidence, providing a comprehensive strategy to optimize the management of osteoporosis in Italy.   On behalf of the Study Group on Osteoporosis and Skeletal Metabolic Diseases of the Italian Society of Rheumatology.